In vitro antimicrobial activity of 3MIX-MP and CTZ pastes against Enterococcus faecalis ATCC® 29212 - Vargas-Mendoza, Jesús Antonio (2023)
Objective. To determine the antibacterial effect of triantibiotic paste (3MIX-MP) and chloramphenicol-tetracycline-ZOE (CTZ) antibiotic paste at 24, 48, 72 hours and 7 days on Enterococcus faecalis. Methods. Experimental, in vitro, comparative study, with a non-probabilistic sample for convenience of 210 paper discs, distributed in 30 Petri dishes previously prepared with Mitis Salivarius agar and Mueller Hinton agar and inoculated with strains of Enterococcus faecalis ATCC® 29212. The method was used. Kirby-Bauer, inoculated with a 0.5 McFarland suspension of Enterococcus faecalis. Filter paper discs were placed inside the wells and 10 µl of antimicrobial pastes and control were supplied. The positive control was zinc oxide-eugenol cement discs; halo diameters were measured with a vernier caliper. A repeated measures ANOVA was used for intragroup comparisons, one-way ANOVA for intergroup comparisons, and Tukey’s post hoc tests. Results. After 24 hours, the 3MIX-MP paste obtained larger inhibition zone diameters than the CTZ paste with an average of 39,24 mm and 34,19 mm, respectively, and a minimum of 36,26 mm and 26,38 mm at 24 hours. 7 days. Statistically significant differences were observed between the halos obtained from the 3MIX-MP paste and the CTZ paste, except for the control after 48 hours. Conclusions. It was determined that the 3MIX-MP paste has a greater inhibitory action in vitro compared to the CTZ paste, the diameter of the inhibitory halos decreased as the exposure time to the microorganism increased.